A randomized controlled trial of interventions for growth suppression in children with attention-deficit/hyperactivity disorder treated with central nervous system stimulants - Waxmonsky, James G.; Babocsai, Lysett (Journal of the American Academy of Child and Adolescent Psychiatry, 2020)
Objective - To examine the impact of central nervous system (CNS) stimulants on the growth of children with attention-deficit/hyperactivity disorder (ADHD), and to assess the efficacy and feasibility of weight recovery interventions on growth. - Method - A total of 230 children aged 5 to 12 years with ADHD with no history of chronic CNS stimulant use were randomly assigned to receive daily CNS stimulants (78%, primarily OROS-methylphenidate [OROS-MPH]) or behavioral treatment (22%) for 30 months. After 6 months, children evidencing a decline in body mass index (BMI) of >0.5 z-units were randomized to 1 of 3 weight recovery treatments (WRTs): monthly monitoring of height/weight (MON) plus continued daily medication; drug holidays (DH) with medication limited to school days; or daily caloric supplementation (CS) with a 150-kcal supplement plus daily medication. - Results - Before WRT assignment, medication was associated with significant reductions in standardized weight and height (p values <.01). Adherence to CS and DH during WRT was high, with significant increases in daily caloric intake and decreases in weekly medication exposure (p values <.05). Across all WRT participants (n = 71), weight velocity increased significantly after WRT randomization (β2 = 0.271, SE = 0.027, p < .001).When analyzed by what parents did (versus what they were assigned to), CS (p < .01) and DH (p < .05) increased weight velocity more than MON. No increase in height velocity was seen after randomization to any WRT. Over the entire study, WRT participants declined in standardized weight (−0.44 z-units) and height (−0.20 z-units). - Conclusion - Drug holidays, caloric supplementation, and increased monitoring all led to increased weight velocity in children taking CNS stimulants, but none led to increased height velocity. - Clinical trial registration information - Novel Approach to Stimulant Induced Weight Suppression and Its Impact on Growth; https://clinicaltrials.gov/; NCT01109849.
Available online 29 August 2019
Gesehen am 16.07.2021